RETRACTED: Ethical Conflict and Knowledge Hiding in Teams: Moderating Role of Workplace Friendship in Education Sector - Xing, Shuo (Frontiers in Psychology, 2022)
Ethical conflicts arise when there is no unity between the team members and shared ethical priorities. This study aimed to identify the relationship between ethical value unity and the team knowledge hiding and the relationship between the lack of shared ethical priorities and the team knowledge hiding. Workplace friendship was taken as a moderating variable to check its regulating role between the ethical conflicts and the team knowledge hiding. Data of this study were collected from the staff working in different colleges and universities. There are a total of 480 responses collected through convenience sampling technique and analyzed under a five-point Likert scale. The partial least squares-structural equation modeling (PLS-SEM) technique is used in this study. The key reason was that this approach has the fewest requirements for data normality and is a better tool for evaluating exploratory connections empirically. The output of the measurement model assessment confirms that all measurement scales are reliable. The result indicates that there was a significant and positive relationship between ethical value congruence and knowledge hiding. It was also established that there was a relationship between lack of shared ethical priorities and knowledge hiding. Workplace friendship moderated the relationship between ethical conflicts and team knowledge hiding. This study extends the literature on ethical conflict and knowledge hiding behavior. This study highlights that one of the main reasons for knowledge hiding behavior at the team level in the organization is which helps the business practicians for a design as an effective strategy to mitigate the knowledge hiding behavior in the organization.